Oxford Word Skills Elementary Vocabulary : learn to use the most important words and phrases in English topic by topic - Gairns, Ruth, ....-; Redman, Stuart, 1950- (Oxford : Oxford university press, 2020)
Based on the Oxford 3000, Oxford Word Skills teaches you the words and phrases you need to use in English in real life. The Oxford 3000 is a list of the 3,000 essential core words that every learner of English need to know, graded by CEFR level.
Keywords: English vocabulary